2013
DOI: 10.1177/1753465813479428
|View full text |Cite
|
Sign up to set email alerts
|

Early life influences on the development of chronic obstructive pulmonary disease

Abstract: There is increasing evidence that chronic obstructive pulmonary disease (COPD) is not simply a disease of old age that is largely restricted to heavy smokers, but may be associated with insults to the developing lung during foetal life and the first few years of postnatal life, when lung growth and development are rapid. A better understanding of the long-term effects of early life factors, such as intrauterine growth restriction, prenatal and postnatal exposure to tobacco smoke and other pollutants, preterm d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 139 publications
(218 reference statements)
1
103
0
2
Order By: Relevance
“…Severe impairments during any (82). However, mild structural or functional defects due to aberrant lung development (83) may increase susceptibility to respiratory diseases (COPD, cystic fibrosis, or asthma) that may be clinically detectable only during childhood or later in life through pulmonary function testing (84)(85)(86)(87). Therefore, it is important to detect genetic abnormalities that can affect early fetal and postnatal lung development; postnatal lung growth and maturation; and lung injury, repair, and remodeling processes (84)(85)(86)(87)(88)(89)(90).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe impairments during any (82). However, mild structural or functional defects due to aberrant lung development (83) may increase susceptibility to respiratory diseases (COPD, cystic fibrosis, or asthma) that may be clinically detectable only during childhood or later in life through pulmonary function testing (84)(85)(86)(87). Therefore, it is important to detect genetic abnormalities that can affect early fetal and postnatal lung development; postnatal lung growth and maturation; and lung injury, repair, and remodeling processes (84)(85)(86)(87)(88)(89)(90).…”
Section: Discussionmentioning
confidence: 99%
“…However, mild structural or functional defects due to aberrant lung development (83) may increase susceptibility to respiratory diseases (COPD, cystic fibrosis, or asthma) that may be clinically detectable only during childhood or later in life through pulmonary function testing (84)(85)(86)(87). Therefore, it is important to detect genetic abnormalities that can affect early fetal and postnatal lung development; postnatal lung growth and maturation; and lung injury, repair, and remodeling processes (84)(85)(86)(87)(88)(89)(90). In mice, alveolarization takes place between P5 and P30 and is controlled by finely integrated and mutually regulated networks of transcriptional factors, growth factors, matrix components, and physical forces (9,(89)(90)(91)(92).…”
Section: Discussionmentioning
confidence: 99%
“…Airway caliber is a key 243 determinant of total airway resistance and reduced caliber is a prominent feature of asthma 244 and chronic obstructive pulmonary diseases (5-7). Lower lung function in early life is likely to 245 lead to lower peak lung function in early adulthood, and the natural decline in FEV1 from that 246 point onwards will be accelerated by any additional adverse exposures (41). Thus, lung 247 function during the lifecourse seems to be programmed at least partly in early life.…”
Section: Early Growth Measures and Lung Function Outcomes 176mentioning
confidence: 99%
“…A growing number of studies suggest that not only cigarette smoke but also several other factors are involved in the pathogenesis of COPD. Alongside those taking effect in adulthood, the role of perinatal and early-infancy factors, including prematurity and BPD, has recently been stressed [161,162], and an association has been suggested between low birth weight and both airflow limitation in adulthood [163,164] and death due to COPD [165]. Likewise, it has been demonstrated that some childhood disadvantages (parental asthma, childhood asthma, childhood respiratory infections and maternal smoking) have much the same impact on adult lung function and the risk of COPD as heavy smoking [50], suggesting that COPD can be seen as a disease of childhood that becomes manifest in adults [124,166].…”
Section: Early Origin Of Copdmentioning
confidence: 99%